YURIDIS TERHADAP TINDAK PIDANA PENGANCAMAN YANG DILAKUKAN SECARA BERSAMA-SAMA - Al Furqon (Jurnal Hukum Volkgeist, 2018)
This research was carried out at the Makassar District Court in Makassar, with research methods using data collection techniques by means of research library and field research. The results of this research indicate that all the elements of a criminal offence committed by the pengancaman the second defendant had sesuasi with the elements contained in article 335 of the PENAL CODE with Article 55 paragraph (1) of the CRIMINAL CODE. This is apparent from satisfy all the elements in accordance with the article didakwakan on the defendant. Article didakwakan, namely Article 335 paragraph (1) of the CRIMINAL CODE. With satisfy the elements and look at the application of the criminal law against the crime pengancaman, then the defendant must account for his actions in accordance with the ruling of the District Court Judges deposed by the Makassar imprisonment of three (3) months and pay the fees. In deciding the matter State Court judge Makassar has pretty much consideration, starting from the demands of the public prosecutor, the accused, description of witnesses, as well as satisfy the elements pursuant to article didakwakan, as well as the things that are incriminating and relieve. So defendants are convicted with imprisonment for 3 (three) months and pay the fees, not fully contain the benefit law. Considering the act committed by the two defendants, then according to the author, the criminal who dropped by the Tribunal of judges rated very lightly.